2008
DOI: 10.1007/s12034-008-0101-6
|View full text |Cite
|
Sign up to set email alerts
|

Dielectrical and structural characterization of iron oxide added to hydroxyapatite

Abstract: In this work we report preparation, structural and dielectric analyses of iron oxide added in hydroxyapatite bioceramic (Ca 10 (PO 4 ) 6 (OH) 2 -HAP). Hydroxyapatite is the main mineral constituent of teeth and bones with excellent biocompatibility with hard and muscle tissues. The samples were prepared through a calcination procedure associated with dry high-energy ball milling process with different iron concentrations (1, 2⋅5 and 5 wt%). The dielectric analyses were made measuring the sample impedance in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…At lower frequency, it was enhanced in incorporated samples perhaps due to the raised ionic polarization. There was reduction in permittivity at higher frequency, possibly due to the lagging of dipole oscillation with the applied field [28][29][30]. The relative permittivity of Mg 2+ ion incorporated HAp enhanced considerably by 99% and 60% compared to FeHAp and BaTiO 3 -HAp respectively [16,31].…”
Section: Real Part Of Relative Permittivitymentioning
confidence: 99%
“…At lower frequency, it was enhanced in incorporated samples perhaps due to the raised ionic polarization. There was reduction in permittivity at higher frequency, possibly due to the lagging of dipole oscillation with the applied field [28][29][30]. The relative permittivity of Mg 2+ ion incorporated HAp enhanced considerably by 99% and 60% compared to FeHAp and BaTiO 3 -HAp respectively [16,31].…”
Section: Real Part Of Relative Permittivitymentioning
confidence: 99%
“…Although only few studies were reported concerning HA‐nano iron oxide composites, the recent report suggests the increased osteoblast density in the presence of nano iron oxide (maghemite) and hence favors its use as a potential candidate in bone tissue engineering applications . But there is a lack in suitable synthetic strategy and proper microstructure evaluation in all the reported methods …”
Section: Introductionmentioning
confidence: 99%
“…Several authors show that they obtain apatite with iron-rich phases dispersed into the crystals. These iron-rich phases have been described as hematite a-Fe 2 O 3 [26], magnetite Fe 3 O 4 [27] or brownmillerite Ca 2 Fe 2 O 5 [28].…”
Section: Introductionmentioning
confidence: 99%